Development of Interactive Learning Media for the Law of Reading Nun Mati and Tanwin at the Tahfidz Zamilatul Qur'an House - Nadia Fahirah; Syahrani Nur Fauziah; Raudhatun Nissa Rusaranha; Akmal Rizki Gunawan Hasibuan (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study was motivated by the lack of understanding among students at Rumah Tahfidz ZamilatulQur'an regarding the rules of reading nun mati and tanwin due to conventional and less interactive learning methods. Tajwid learning, which predominantly uses lectures and written exercises, causes students to lack motivation and often make mistakes in reading rules such as idgham, ikhfa, and iqlab. The purpose of this study is to develop effective, interesting, and interactive learning media that are in line with the learning characteristics of tahfidz students in order to improve their understanding and interest in learning tajwid. This study uses a qualitative approach, with the research subjects consisting of tahfidz teachers and students at Rumah Tahfidz Zamilatul Qur'an. Data was collected through observation and interviews, then analyzed. The results show that the technology-based interactive learning media developed received positive responses from teachers and students. This media is considered effective because it is able to present the rules of reading nun mati and tanwin visually and auditorily through letter animations, audio pronunciation, interactive exercises, and evaluations. The application of this media also increases the motivation, active involvement, and accuracy of students' pronunciation in reading the Qur'an.